Reversible light-dependent molecular switches on Ag/AgCl nanostructures - Song, W.; Querebillo, C. J.; Goetz, R.; Katz, S.; Kuhlmann, U.; Gernert, U.; Weidinger, Inez M.; Hildebrandt, Peter (Nanoscale, 2017)
Nanostructured Ag/AgCl substrates were used to generate reversible and highly efficient light-dependent chemical switches based on adsorbed 4,4′-dimercaptoazobenzene (DMAB). DMAB was formed in situ via laser-induced dimerization either from 4-nitrothiophenol (4-NTP) or 4-aminothiophenol (4-ATP). The subsequent reaction pathways of DMAB, however, were quite different as monitored by surface enhanced Raman spectroscopy. In the 4-NTP/DMAB system, AgCl catalyses the reversal of the dimerization. Conversely, irradiation of adsorbed 4-ATP first generated cis-DMAB attached to the surface via two Ag-S bonds, followed by AgCl-catalysed cleavage of one Ag-S bond and cis → trans photoisomerisation of DMAB. In the dark, the trans-isomer thermally reverts to cis-DMAB. The here presented light-dark chemical switches, which work without changing other parameters (e.g., pH, anaerobic vs. aerobic), are based on the (photo)catalytic properties of the Ag/AgCl substrate and do not function on pure metal surfaces.
CRIS-Team Scopus Importer:2022-04-14